The spirit of Albion : an anthropological study of the Order of Bards, Ovates & Druids - Lakey-White, R (2009)
Since the 1990s, a new form of spirituality has been spreading throughout the western world. Called 'Druidry', this spirituality is based on what is known of ancient Celtic beliefs and practices. This spirituality is not merely archaising; rather, it seeks to incorporate the Zeitgeist of the ancient Celts into a new (and admittedly modern) practice that holds meaning for its adherents. Ethnographic research for this work was conducted with one of the most prominent modern Druid organizations, the Order of Bards, Ovates & Druids. This organization was chosen as it was founded by modern Druidry's progenitor, Ross Nichols. While many other Druid groups exist, this group is arguably the largest worldwide. Although modern Druidry is practiced in such geographically disparate regions as New Zealand, Australia, the United States and Europe, I focus on the movement in Britain, as it is the home of OBOD's international organization and it is arguably the country with the greatest number of Druid gatherings and the largest community of currently practicing members. Research was conducted with many different members of the organization, but concentrated on one of OBOD's 'groves', the Anderida Grove of the Seven Hills. This thesis was conceived primarily as an ethnographic study of an emergent spirituality, with a particular emphasis on the continual confrontation within modern Druidry between the ancient and the modern. As such, the work focuses on describing and analysing modern Druid belief and practice, including discussions regarding such areas as ritual and myth. However, the modern Druid evidence can also lead anthropologists to a deeper understanding of certain key debates current within the discipline of anthropology. I have chosen to focus primarily on how nationalism and ethnicity are synthesised through the mechanism of the 'invention of tradition' to create what modern Druids refer to as 'the tribe'.